Imobilização de peptidases laticíferas em diferentes suportes para aplicação na hidrólise de alérgenos do leite bovino - Oliveira, João Pedro Brasil de (2022)
Milk allergy is a public health problem that affect mainly the infants. For these, hydrolyzed formulas become the main source of nutrients. In this context, the aim of this study was to develop biocatalysts by the immobilization of peptidases from the latex of Calotropis procera (CpCPs) on different supports, aiming the hydrolysis of allergenic proteins of bovine milk. CpCPs were rapidly immobilized on sulfopropyl-agarose (support with negative charge), but with low recovered activity (4%). When immobilizations of CpCPs were performed on MANAE-agarose and DEAE-agarose (supports with positive charge), yield of 33% and 54% and recovered activities of 23% and 20% were observed, respectively. Covalent immobilizations were performed on glyoxyl-agarose and MANAE-agarose (activated with glutaraldehyde, MANAE-GLU). Using glyoxyl (glyoxyl-CpCPs), the immobilization yield was approximately 100%, with recovered activity of 11%. However, when L-cysteine was used in the immobilization [glyoxyl-CpCPs(Cys)], recovered activity of 60% was obtained. Immobilization on MANAE-GLU generated different biocatalysts with high yield (> 90%) and recovered activity (> 200%), that latter was obtained using BANA as substrate. Regarding the characterization of the biocatalysts, CpCPs immobilized in glyoxyl was stable at acidic pH values; while CpCPs immobilized in MANAE (by adsorption or covalently) caused a change of the optimal pH for enzymatic activity to more basic pH values, compared to soluble CpCPs. Regarding thermal stability, CpCPs immobilized in glyoxyl were 60-fold more stable at 60 °C and pH 10.0, when compared to soluble CpCPs. After five reaction cycles, the residual activity was 90%, 70%, 60% and 30% for MANAE-GLU-CpCPs, glyoxyl-CpCPs, glyoxylCpCPs(Cys) and MANAE-CpCPs, respectively. The kinetic parameters of glyoxylimmobilized CpCPs were evaluated. It was observed that glyoxyl-CpCPs presented Km and Vmax values close to soluble CpCPs; while glyoxyl-CpCPs(Cys) showed low values of Km and Vmax. FTIR analyzes exhibited changes in the bands corresponding to amide I and II, which may suggest alteration of CpCPs secondary structure after immobilization. Regarding the hydrolysis of milk proteins, CpCPs immobilized on glyoxil was able to extensively hydrolyze the caseins (residual allergenicity - 3%) and partially hydrolyze the whey proteins (residual allergenicity - 35%), showing greater efficiency when compared to a commercial partially hydrolyzed formula (Enfamil Gentlease). Furthermore, CpCPs immobilized on glyoxyl was efficient in the hydrolysis of milk proteins for at least 5 reaction cycles. Thus, it can be concluded that the immobilization of CpCPs resulted in biocatalysts with promising potential for application in the hydrolysis of proteins from bovine milk for the production of hypoallergenic formula